The complete mitogenome of Eucryptorrhynchus brandti (Harold) (Insecta: Coleoptera: Curculionidae). (3rd May 2016) - Nan, Xiaoning; Wei, Cong; He, Hong
Abstract: The complete mitochondrial genome of Eucryptorrhynchus brandti (Harold) (Insecta: Coleoptera: Curculionidae) were reconstructed from whole-genome Illumina Hiseq 2000 sequencing data with an average coverage of 1406.7X. The circular genome is 15, 122 bp in length, consisting of 13 protein-coding genes (PCGs), 21 transfer RNAs (tRNAs), two ribosomal RNAs (rRNAs) and one D-loop or control region. The tRNA-Ile gene was not found in the mitochondrial genome, as is identical to two other curculionidae species, i.e. Sphenophorus sp . (GU176342) and Naupactus xanthographus (GU176345). All PCGs initiated with ATN codons, except for the ND1 started with TTG. Two PCGs ( COI and ND4 ) have an incomplete stop codon T. Two PCGs ( ND4L and ND1 ) harbor the stop codon TAG, while all other PCGs terminated with the TAA codon. The nucleotide composition is highly asymmetric (38.7% A, 14.4% C, 9.2% G and 37.8% T) with an overall AT content of 76.5%.